Molecular diagnostics - Patrinos, George P.; Ansorge, Wilhelm, 1944- (Elsevier/Academic Press, 2010)
Key Features . Contains state-of-the-art techniques for the detection of the underlying genetic heterogeneity leading to inherited disorders . Includes in-depth discussion of ethical and safety considerations . Identifies genetically modified organisms (GMO's) . Covers forensic analysis and every-day issues in a diagnostic laboratory Description The second edition of Molecular Diagnostics, the only book dealing with diagnosis on a molecular level, discusses current molecular biological techniques used to identify the underlying molecular defects in inherited disease. The book delves further into the principle and brief description of the technique, followed by examples from the authors' own expertise. Contributors to the 2/e are well-known experts in their field, and derive from a variety of disciplines, to ensure breadth and depth of coverage. Molecular Diagnostics, 2/e, is a needed resource for graduate students, researchers, physicians and practicing scientists in molecular genetics; professionals from similar backgrounds working in diagnostic laboratories in academia or industry, as well as, academic institutions and hospital libraries. RELATED TITLES: Trent/Molecular Medicine, April 2005,$79.95, 0-12-699057-3 Innis (1999) PCR Applications, HB, $89.95,0-12-372185-7, PB, $66.95, Key Features: *Deals exclusively with the currently used molecular biology techniques to identify the underlying molecular defect of inherited diseases *Includes pharmacogenetics and pharmacogenomics relating to new cancer therapies *Provies a comprehensive guide through emerging concepts and demonstrates how the available mutation screening technology can be implemented in diagnostic laboratories and provide better healthcare.